Femicid - Podreka, Jasna (Annales. Series historia et sociologia, 2019)
Based on the empirical findings that most of the murders and violent deaths of women are the result of some form of gender-based violence, the authors of the article point to the importance of introducing a specific terminology for the naming of violent deaths of women, namely the term femicide. The subject of femicide is a rather neglected research field in Slovenia, since the concept and the history of the emergence of this notion are quite unknown to us. Therefore, the purpose of this paper is to present the evolution of the definition and discussion on justification to introduce the notion of femicide for naming the sexually-marked violent deaths of women. Through the presentation of important findings from numerous studies at home and abroad, they show that there are significant gender differences in violence against women ("gender-based violence"), as well as in the murder and violent deaths of women. At the same time, this paper attempts to answer the question, why the introduction of the term femicide to name the violent deaths of women and murders seems necessary and justified. They are based on the assumption that the naming and definition of newly identified forms of oppression of women is of key importance for solving and preventing such problems.
Keywords: femicid; intimnopartnerski odnosi; intimnopartnersko nasilje; Moški; Nasilje; partnerske zveze; spolna neenakost; terminologija; Umori; Ženske